ANALISIS SWOT SEBAGAI DASAR DALAM MENENTUKAN STRATEGI PEMASARAN PADA PERUSAHAAN PT.HARMONY TOBA JAYA MEDAN - Siregar, Ninny (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2016)
PT. Harmony Toba Jaya is one of the paint distributor with Sikkens trademark. Companies choose direct communication with consumers workshops in their marketing communications strategy. This is done because of the increasing number of new paint products on the market so we need a strategy that is relevant to the condition that there is a bottom -up with a marketing strategy where marketers sell products directly to end users or workshop. Based on the above conditions need to be processing data analysis using SWOT analysis (Strength, Weakness, Opportunity and Threat) from Sikkens paint products through questionnaires given to consumers. Based on the results of the questionnaire processing, can be calculated the value of the X axis and Y axis to determine the position of the company. The value of the X- and Y-axis respectively is -0.141 and -0.100 so that the value of the intersection of the axes X and Y are XY (-0.141; -0.100). From these results, the company is located in Quadrant IV (negative, negative). It is necessary to get attention because in addition to the weakness of the company there are also threats from competitors that are very dangerous. Therefore, recommendations given strategy is Strategy Defense, meaning that the internal conditions of the organization that are in selection dilemma. Therefore, organizations are advised to use a survival strategy, the performance of internal control so as not to fall. This strategy is maintained while trying to fix ourselves.Keywords: Marketing Strategy, SWOT Analysis, Company Position